HUBUNGAN PERANAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN KOMPETENSI PEDAGOGIK GURU DI SMK NEGERI 2 KOTA PADANG - Nellitawati Nellitawati Yusof Bin Boon (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
This research about leadership role of headmaster and pedagogy competencies of teacher in SMK 2 Padang, and also to see the relationship between the two variables. Population are 72 teachers and 40 samples using proportional stratified random sampling technique. This research instrument is a questionnaire in the form of a Likert scale, a score of variable leadership role of headmaster 0.907 and pedagogy competencies of teacher 0.897 that means instrument is reliable. Data were analyzed using product moment correlation, get r score = 0.33 > = 0.284 believed r tabel standard 95%. Research has come to the conclusion that there are relationship between leadership role of headmaster with the pedagogy competencies of teacher in SMK Negeri 2 Padang.